Parametric modelling of radiation forces for marine offshore renewable energy systems: A Loewner-based approach (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Marine offshore renewable energy systems are virtually always modelled by exploiting numerical solvers in the frequency domain, characterising the device hydrodynamics for a finite set of user-defined frequency components.  A well-known limitation of this frequency-domain approach, nonetheless, is its inherently non-parametric nature, which complicates its use in time-domain simulation and modern control design. These tasks almost always require compact parametric models--typically in state-space form--to enable system analysis, synthesis, and real-time control implementation. Motivated by this, we present, in this paper, a frequency-domain parameterisation framework for representing the radiation dynamics of floating structures in marine renewable energy systems. The approach, based on the underpinning theory of Loewner matrices, is able to construct reduced-order parametric models directly from raw frequency-domain data, typically obtained from boundary element methods (BEMs). To demonstrate its effectiveness, a detailed case study is presented, based on a hybrid wind–wave energy converter, showcasing the accuracy and versatility of the proposed approach across two major renewable energy sectors. We show that the resulting models successfully capture complex radiation interactions while preserving the essential physical properties of radiation effects.